2018
DOI: 10.3892/ijo.2018.4564
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase HDAC4 promotes the proliferation and invasion of glioma cells

Abstract: Glioma is the most lethal type of primary brain tumor characterized by aggressiveness and a poor prognosis. Histone deacetylase 4 (HDAC4) is frequently dysregulated in human malignancies. However, its biological functions in the development of glioma are not fully understood. The present study aimed to evaluate HDAC4 expression in human glioma and to elucidate the mechanistic role of HDAC4 in glioma. The results suggested that HDAC4 was significantly upregulated in glioma tissues and a number of glioma cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…When HDAC4 was overexpressed in U251 cells, the glioma cell's invasive ability was enhanced. By inhibiting the expression of HDAC4 in U251 cells, the invasive ability was diminished [7]. These findings from previous research support the use of HDAC4 as a therapeutic target for glioma, as inhibition of this enzyme would result in decreased proliferation and invasiveness of this tumor type.…”
Section: Hybrid Compoundssupporting
confidence: 69%
See 2 more Smart Citations
“…When HDAC4 was overexpressed in U251 cells, the glioma cell's invasive ability was enhanced. By inhibiting the expression of HDAC4 in U251 cells, the invasive ability was diminished [7]. These findings from previous research support the use of HDAC4 as a therapeutic target for glioma, as inhibition of this enzyme would result in decreased proliferation and invasiveness of this tumor type.…”
Section: Hybrid Compoundssupporting
confidence: 69%
“…It has been shown that increased levels of HDAC4 decrease HDAC4, which is elevated in glioma cells, has been demonstrated to be essential for tumorigenesis of glioma. When HDAC4 was knocked down in U251, a human gliomablastoma cell line, the proliferation ability of the cells was significantly decreased [7]. When HDAC4 was overexpressed in U251 cells, the glioma cell's invasive ability was enhanced.…”
Section: Hybrid Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Kang et al purported that HDAC4 accelerated cell progression of gastric cancer via inhibiting p21 15 and Cai et al found the oncogenic role of HDAC4 in glioma. 16 Also, HDAC4 has been testified to enhance OS cell proliferation and invasion, 17 but its association with miR-432-5p and circCRIM1 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of HDAC4 and HDAC5 was downregulated in high-grade gliomas when compared with low-grade ones, and was associated with a favorable clinical outcome [17,18]. Interestingly, HDAC4 and HDAC5 have been reported to act as oncogenes by promoting the proliferation of glioma cells, as well as their invasive ability [19,20]. KAT2A, also known as GCN5, functions primarily as a transcriptional activator, although it also represses NF-κB signaling by promoting the ubiquitination of the NF-κB subunit RELA [21].…”
Section: Discussionmentioning
confidence: 99%